Active Middle Ear Implant Evoked Auditory Brainstem Response Intensity-Latency Characteristics - Fröhlich, Laura; Müller, Alexander; Kropp, Miriam H.; Mir-Salim, Parwis; Dziemba, Oliver; Oberhoffner, Tobias; Plontke, Stefan K.; Rahne, Torsten (Frontiers in Neurology, 2022)
Objective: To analyze intensity-latency functions of intraoperative auditory evoked brainstem responses (ABRs) to stimulation by the Vibrant Soundbridge (VSB) active middle ear implant with respect to coupling efficiency, VSB evoked ABR thresholds, and coupling modality (oval window [OW] placement versus Incus placement and versus round window [RW] placement). Study design: Exploratory study. Setting: Bi-centric study at tertiary referral centers. Patients: Twenty-four patients (10 female, 14 male, mean age: 58 years) who received a VSB. Outcome Measures: Wave-V intensity-latency functions of intraoperative VSB evoked ABRs using a modified audio processor programmed to preoperative bone conduction thresholds for stimulation. Threshold level correction to coupling efficiency and ABR thresholds. Individual plots and exponential function fits. Results: After ABR threshold level correction, the latency functions could be aligned. A large variance of latencies was observed at individual threshold level. Wave-V latency was longest in the Incus placement subgroup (9.73 ms, SD: 1.04) as compared to OW placement subgroup (9.47 ms, SD: 1.05), with the shortest latency in the RW placement subgroup (8.99 ms, SD: 0.68). For increasing stimulation levels, the variance decreased with intensity-latency function slopes converging towards a steady-state (saturation) latency caused by saturation of audio processor (stimulation) gain. Latency saturation was reached at a stimulation level of 50 dB nHL for the OW placement subgroup, 35 dB nHL for the Incus placement subgroup, and 30 dB nHL for the RW placement subgroup. The latency and saturation results indicated decreased dynamic range for RW placement, i.e., reverse stimulation. Conclusions: VSB evoked ABR wave-V intensity-latency function slopes were similar to acoustic stimulation at high stimulation levels with a shift towards longer latencies caused by audio processor signal delay. Saturation of latencies occurred for higher stimulation levels due to saturation of audio processor gain. Thus, the analysis of VSB evoked intensity-latency functions appears to allow for the objective assessment of a patient’s individual dynamic range. This can further improve diagnostics as well as intraoperative and postoperative quality control.